A modern teacher as a subject of students' civil identity formation - O. V. Berezhnaya; A. L. Kobleva (Вестник Северо-Кавказского федерального университета, 2023)
The article discusses the role of a teacher as the subject of the formation of the foundations of students' civic identity. In order to determine the professional and personal characteristics of a teacher, which are necessary for solving the problems of civic education, psychological and pedagogical studies devoted to the definition of the concepts of «identity», «civil identity», «professional and personal portrait of a teacher» have been studied and analyzed. And also, ideas about what features a teacher themselves should have, as a patriot of their profession, conscientious and responsible for the formation of value orientations of the younger generation, are analyzed. The integration of the basic components of the civil position of a teacher has been established: spiritual and moral culture, professional competencies and motivation. Thus, the main components of the teacher's characteristics are revealed, confirming his professional and personal readiness to create the necessary conditions for students to comprehend their «I», as a citizen of Russia. The article substantiates the idea of the leading role of a modern teacher, who is able to act as the subject of the formation of students' civic identity, in an open semi-subjective educational environment. Comparative and integration analysis of the results of scientific-theoretical, methodological works and pedagogical experience in the field of forming the foundations of civic identity among students leads to the conclusion that the social role of the teacher, a priori, is the leading one in solving this educational problem. At the same time, attention is also drawn to the fact that despite numerous studies on this issue, to date, the components of the teacher’s professional and personal readiness to solve the problems of civic education are still poorly understood. It requires further forecasting of the goals and objectives of the teacher training system, as well as constructing models for leveling the professional deficits of teachers in this area of pedagogical activity.